The Alignment, Interest and Influence Matrix (AIIM) guidance note - and Mendizabal, Enrique (ODI/RAPID, 2010)
In 2007, on the eve of a workshop to introduce a new version of the RAPID approach to DFID policy teams, Enrique Mendizabal and Ben Ramalingam created the Alignment, Interest and Influence Matrix (AIIM), a stakeholder analysis tool that not only helps to identify key stakeholders, but also suggests a possible course of action towards them.